2003
DOI: 10.1073/pnas.1633724100
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone (DHEA) prevents and reverses chronic hypoxic pulmonary hypertension

Abstract: Pulmonary artery (PA) hypertension was studied in a chronic hypoxic-pulmonary hypertension model (7-21 days) in the rat. Increase in PA pressure (measured by catheterism), cardiac right ventricle hypertrophy (determined by echocardiography), and PA remodeling (evaluated by histology) were almost entirely prevented after oral dehydroepiandrosterone (DHEA) administration (30 mg͞kg every alternate day). Furthermore, in hypertensive rats, oral administration, or intravascular injection (into the jugular vein) of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
121
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 30 publications
12
121
1
Order By: Relevance
“…One study has shown that exogenous estrogen exposure protected pulmonary hypertensive rats from pulmonary vascular remodeling and right ventricular hypertrophy [28]. Also, DHEA, a testosterone precursor, has been shown to prevent and reverse pulmonary artery remodeling [31].…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that exogenous estrogen exposure protected pulmonary hypertensive rats from pulmonary vascular remodeling and right ventricular hypertrophy [28]. Also, DHEA, a testosterone precursor, has been shown to prevent and reverse pulmonary artery remodeling [31].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in HMC-1 intracellular calcium concentration were assessed using the Ca 2ϩ -sensitive probe indo-1 as described previously (13,16). Briefly, cells were loaded with indo-1 (Calbiochem) and mounted in a perfusion chamber continuously perfused.…”
Section: Microspectrofluorimetrymentioning
confidence: 99%
“…The active dose of DHEA used in our experiments is identical to that given in our previous studies (9,21). This chronic oral protocol yields a circulating concentration of DHEA in the range of ≥10 −7 mol/l, similar to that commonly used in in vitro studies.…”
Section: Discussionmentioning
confidence: 74%
“…In different models of adult rats with PH, we (9) and others (10,11) have shown that DHEA prevents and reverses PH and the resulting right-ventricular (RV) hypertrophy as well as small PA remodeling. However, similar studies have not been performed in newborn or infant animals.…”
mentioning
confidence: 96%
See 1 more Smart Citation